(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Geometric Function Theory which is one of the branches of Complex Analysis relating to certain studies on interesting results connected with Geometry and Analysis. We propose certain properties of Geometric Function Theory with special applications. Geometric Function Theory deals with several physical properties like defining the magnetic field, electromagnetic field, signal processing and wavelets based on the significant classes of functions with reference to analytic functions.